UUM gets international accreditation - The, Sun (The Sun, 2016)
SINTOK: Thirty-two years after it was set up, Universiti Utara Malaysia (UUM) has attained a major achievement when it gained global accreditation from the renowned Association to Advance Collegiate Schools of Business (AACSB).